Regular globally hyperbolic maximal anti‐de Sitter structures. Issue 1 (29th January 2020) - Tamburelli, Andrea
Abstract: Let Σ be a connected, oriented surface with punctures and negative Euler characteristic. We introduce regular globally hyperbolic anti‐de Sitter structures on Σ × R and provide two parameterisations of their deformation space: as an enhanced product of two copies of the Fricke space of Σ and as the bundle over the Teichmüller space of Σ whose fibre consists of meromorphic quadratic differentials with poles of order at most 2 at the punctures.